Educar de cara a la existencia - Romero Oñate, Luis (Mercurio Peruano, 2011)
In the light of the multiplicity of perspectives: sociological, culturalist, historical, psychological or biomedical; with which human reality can be understood, we here state the convenience of understanding education from a metaphysical vision which considers the person as a whole with unity. Existence is not limited to some sort of instinctive dynamisms no matter how complex they are, but it is presented as an untransferable task oriented towards the pursuit of happiness. Thus, education is not limited to the transmission of knowledge and attitudes, since a similar approach necessarily leads to a man fragmented in isolated dimensions. Education when aimed at existence must be wisdom, which without being imposed helps the person to develop as a person. This is only possible in the horizon of religion, which also includes a way of behaving which is apprehension of history, of literature, of art, of science, etc. Virtues are the operational resources which allow for the effective realization of harmony.